Pengembangan Model Pelayanan Kesehatan dan Sosial Berbasis Komunitas bagi Lansia - Damayanti Suhita; Riska Wirawan (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The increasing elderly population in Indonesia demands integrated health and social services. Posyandu Lansia plays a strategic role for society, yet Posyandu Lansia Lenggono RW 25 Mojosongo lacked a comprehensive model covering physical, mental, social, and spiritual aspects. This project aimed to develop a community-based service model using a Participatory Action Research (PAR) approach, including needs assessment, model design, cadre training, implementation, and evaluation. Results show elderly participation increased from 35% to 72%, while cadre capacity improved by 48% based on post-test scores. The model integrates elderly exercise, health and psychosocial counseling, spiritual guidance, reminiscence therapy, home visits, and a structured data recording system. These findings confirm that community-based approaches effectively improve service quality. Cadre involvement, family support, and institutional backing are key to sustainability, and the model is replicable in other areas